2018
DOI: 10.1039/c8sc00024g
|View full text |Cite
|
Sign up to set email alerts
|

Sequential electron transfer governs the UV-induced self-repair of DNA photolesions

Abstract: QM/MM simulations elucidate the self-repair mechanism of the cyclobutane pyrimidine dimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 78 publications
(78 reference statements)
4
52
0
Order By: Relevance
“…Finally, once the negative charge is transferred to the T=T dimer, it induces breaking of the C5–C5 bond in the S 1 (CT)/S 0 state crossing. The remaining C6–C6 bond of the CPD is opened spontaneously in the vibrationally hot electronic ground state 28 , as schematically demonstrated in Fig. 1 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Finally, once the negative charge is transferred to the T=T dimer, it induces breaking of the C5–C5 bond in the S 1 (CT)/S 0 state crossing. The remaining C6–C6 bond of the CPD is opened spontaneously in the vibrationally hot electronic ground state 28 , as schematically demonstrated in Fig. 1 .…”
Section: Resultsmentioning
confidence: 92%
“…Previous theoretical works reported that charge-transfer (CT) electronic states in the GAT=T sequence are characterized by high vertical excitation energies and populated only indirectly, outside of the Franck–Condon region of the oligomer 28 , 29 . Therefore, involvement of an alternative nucleoside acting as a prebiotic flavin mimic could significantly lower the excitation energies of CT states and increase the self-repairing activity of oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…A fourth decay channel was found as well, which is however blocked by a 0.5 eV barrier arising due to a stabilizing inter-base excitonic state. Similarly, Szabia et al recently reported in a QM/MM study a UV-induced repair mechanism for Cyclobutane pyrimidine dimers (CpDs) formed by thymine dimerization 34 . There are also several QM/MM studies combined with ground-state molecular dynamics (MD) simulations using accurate ab-initio and semiempirical methods 21,24,35 .…”
Section: Introductionmentioning
confidence: 81%
“…This is due to asymmetric T 3 -T 5 stacking orientation, leading to different monomer-like decay paths, arisen from non-equivalent electronic, electrostatic and sterical interactions. In the same way, different stacking ways should give, for the same reason, additional modified decay paths, as recent publications demonstrate [35][36] . The upper part of Figure 1 shows T 5 and T 3 ring puckerings leading the out of plane methyl motion vs. T 3 and T 5 respectively: they are called T 5 QM and T 3 QM mechanisms, shown in Figure 1a and 1b respectively.…”
mentioning
confidence: 81%
“…This is a realistic model of DNA considering that dimeric excitons dominate the photon absorption process 33 either in homo-and hetero-DNA multimers that show at least two stacked homo-bases. Four different intra-base ππ* decay routes accounts for all the possible classical 'ethene-like' mechanism, due to the asymmetric environment experienced by Thys in B-DNA 31,35 . Three of them roughly resemble the decay path energy profile found in isolated solvated nucleosides, showing a very flat decay path with a tiny barrier along the ring-puckering/methyl-bending reaction coordinate, and accounting for the two ultrafast (τ 1 and τ 2 ) decay components observed.…”
Section: Qmmentioning
confidence: 99%